USAHA HOME INDUSTRI CAMILAN KRIPIK JAMUR KRISPY SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT - Agung Suprojo; Noora Fithriana (Universitas Tribhuwana Tunggadewi, 2018)
Oyster mushroom is an organic plant rich in nutritional content and highly nutritious for the human body. Oyster mushroom has the potential as an anti-tumor, anti-fungal, immune system regulator, as well as to reduce the effect of blood lipids and blood sugar. In addition, this mushroom also helps to nourish the environment. Utilizing or managing oyster mushrooms into various forms of snacks is an effort in order to realize community empowerment. The method used in this activity was collecting IRT KingKres and IRT Indo Jamur in one location of the same activity, and each partner group was given counseling and business assistance. The result of Science and Technology for Society showed that the activity was done with good preparation, and done with good cooperation between program implementer and partner community and held entrepreneurial socialization. The impact of this program has been to increase economic independence, especially on the productivity and income of the people who get help. Keywords: business group, snack, krispy mushroom chips